Pengalaman Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisis Dalam Mengatasi Keluhan Yang Dirasakan Di Murni Teguh Memorial Hospital - Sitompul, Kristin Natalia; Simatupang, Lenny Lusia (Universitas Murni Teguh, 2024)
Hemodialysis is a treatment that can prevent death but cannot cure nor compensate for the loss of kidney metabolism or endocrine activity, and the impact of the kidneys and their treatment on quality of life. Hemodialysis results in various biopsychosocial complications that require health professionals to understand and be able to provide holistic services. The aim of this research is to explore and explore the experiences of chronic kidney failure patients undergoing hemodialysis in dealing with their complaints. This research is qualitative research with a descriptive phenomenological study. Data collection was carriedout using in-depth interviews. There were 10 participants in this study who were selected using a purposive sampling technique, participants who underwent hemodialysis for more than 6 months and were more than 18 years old. The interviews were carried out at Murni Teguh Memorial Hospital, the researcher had a contract with the participants and the researcher visited the participants while they were undergoing dialysis. The interview results were analyzed using the Miles and Huberman method and 5 themes were found in the results of the interviews with the participants. The themes found were (1) the causes of hemodialysis (dialysis), (2) experiencing physical, psychological, social complaints and disruption of spiritual activities following, (3) trying to find medical and traditional therapy to overcome the complaints felt, (4) obstacles hemodialysis patients in following a diet and limiting fluids, (5) satisfaction of hemodialysis patients in carrying out routine dialysis at Murni Teguh Memorial hospital. Based on the research results, it is recommended that nurses in providing nursing services be able to provide services with a great sense of empathy and pay attention to patient care holistically (psychosocial spiritual) so as to achieve better service and increase the enthusiasm of patients with hemodialysis in undergoing therapy regularly.